Interaction of Credit and Market Risks and Impact on Banks’ Economic Capital - Hassanein, Medhat; Mohammed Bouaddi; Aziz, Heba Mohamed Abdel (Archives of Business Research, 2023)
Banks often measure the magnitudes of credit and market risks separately, and then add up the two to estimate economic capital. This approach ignores the complex interactions between the two risk types. We develop a model in which these risks are estimated jointly. We used both Value at Risk (VaR) and Conditional Value at Risk (CoVaR) risk measures to analyze the relation between market and credit risks interconnectedness among banks during financial stress. Our model is based on the market returns and total provisions in 37 banks in Asia, Europe, and North America. The results show that deliberately ignoring the interaction between these types of risk leads to either an under or overestimation of the sum of the magnitudes of the two risks, and hence, results in an over or underestimation of economic capital. It was concluded that during times of financial distress, an increase in a bank’s provision would lead to an extreme loss in stock returns that were higher than the VaR value. This proves that underestimating credit risk can lead to an increase in the market risk faced by banks during financial distress.